(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
Currently, in the context of accelerating industrialization, modernization and international integration, especially when Vietnam is in the period of the industrial revolution 4.0 (Industry 4.0), the issue of human resources is considered a breakthrough stage, human resource development becomes the foundation for sustainable development and increases the national competitive advantage. With the advantage of being in the golden population period, Vietnam’s human resources today will not only have their own advantages but also have significant challenges in the 4.0 industrial revolution. It should be frankly acknowledged that the training of human resources in recent years has made clear changes, but it has not been as expected and has not met the requirements of the economy. Therefore, the inevitable problem in the Industrial Revolution 4.0 is improving the quality of human resource training. The article focuses on analyzing the current situation and solutions to enhance the quality of human resource training in Vietnam to meet the requirements of Industrial Revolution 4.0